1978
DOI: 10.1085/jgp.72.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Voltage- and time-dependent action of histrionicotoxin on the endplate current of the frog muscle.

Abstract: A B S T R A C T Histrionicotoxin, a toxin isolated from skin secretions of a Colombian arrow poison frog, Dendrobates histrionicus, decreased the amplitude and timecourse of the endplate current, and altered the voltage dependence of the halfdecay time. In addition, the toxin produced a characteristic nonlinearity in the current-voltage relationship of the endplate current when 3-s voltage conditioning steps were used. Reduction in time of the conditioning steps to 10 ms made the current-voltage relationship l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…The elimination ofthe nonlinearity in the I/V relationship ofthe epc (1 and 2 ,M) when the membrane potential was changed from the holding potential at -50 mV to the extremes of +50 mV and -150 mV, using 3- (1981) 5243 by using voltage sequence B suggests that the nonlinearity observed when sequence A is used is independent of AcCho receptor activation. In this respect, the results produced by these agents are qualitatively similar to the effects of histrionicotoxin and phencyclidine on epc amplitude (5,6). reps remained unaltered whether voltage sequence A, B, or C was used.…”
Section: Methodssupporting
confidence: 62%
See 2 more Smart Citations
“…The elimination ofthe nonlinearity in the I/V relationship ofthe epc (1 and 2 ,M) when the membrane potential was changed from the holding potential at -50 mV to the extremes of +50 mV and -150 mV, using 3- (1981) 5243 by using voltage sequence B suggests that the nonlinearity observed when sequence A is used is independent of AcCho receptor activation. In this respect, the results produced by these agents are qualitatively similar to the effects of histrionicotoxin and phencyclidine on epc amplitude (5,6). reps remained unaltered whether voltage sequence A, B, or C was used.…”
Section: Methodssupporting
confidence: 62%
“…Because our initial experiments with the tricyclic antidepressants (10, 11) disclosed a voltage-and time-dependent effect on epc amplitude, we decided to investigate these voltage-and time-dependent effects by using various membrane potential conditioning sequences (6,20). Voltage sequence A was similar to that used to examine the effect ofhistrionicotoxin on epcs in frog sartorius muscles (6). The sequence consisted of 10-mV steps from an original holding potential of -50 mV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At higher concentrations (400 gM and above) the decay phase was often split into a fast and a slow exponential component, as found by Milne & Byrne (1981) (Adams, 1977;Masukawa & Albuquerque, 1978;Tiedt et al, 1979;Adams & Feltz, 1980a, b) and on autonomic ganglion cells (Ascher et al, 1979;Rang, 1982) (Jenkinson, 1960;Colquhoun et al, 1979) and gallamine (Colquhoun & Sheridan, 1982) has been shown to be insensitive to membrane potential. Colquhoun & Rang (1976) Pennefather & Quastel, 1981).…”
Section: Resultsmentioning
confidence: 60%
“…These matched pairs of muscles were used because the toxin washes out of muscle so slowly that tests of the two enantiomers on the same muscle are impossible. To prevent twitch, glycerol shock was used [12-141. The technique for EPC experiments and analysis is described elsewhere [13,14]. It has been shown [6] that 10pM Hiz-HTX reduces EPC peak amplitude to about 50% of the control value.…”
Section: Methodsmentioning
confidence: 99%